A critical approach to wage devaluation: The case of Spanish economic recovery. Issue 1 (1st March 2019) - Bilbao-Ubillos, Javier; Fernández-Sainz, Ana
Abstract: In line with the orientation of EU economic policy, the Spanish government has favoured a strategy of internal devaluation as a way of adjusting price levels within the currency union. The results of empirical studies indicate that the internal devaluation applied in Spain does not seem to have attained the desired goals in terms of reducing the relative prices of exports and consolidating a model of growth based on external demand. Indeed, the estimates drawn up show that tailwinds – the depreciation of the euro and the fall in risk premium as results of the measures taken by the ECB, greater economic activity by trading partners and the fall in the price of oil – exercised a decisive influence in the trends followed by the prices of exports and the balance of trade during the period of crisis management in Spain.